Jedna, wiele czy może żadna? Fenomenologia w naukach o wychowaniu. Wątki fenomenologiczne w naukach o wychowaniu – kontekst historyczny - Piotrowski , Paweł (Studia Edukacyjne, 2017)
The article presents and reflects on the presence of some phenomenological motifs in educational sciences research and investigations. The text focuses on historical, methodological and structural context of this connection. An attempt is made to assert qualification conditions for each of the answer options mentioned in the title, as possible answers to the question about the connection between phenomenology and educational science. An attempt to define reasons for each of the above answers is taken as well.